Food and Fantasy in Early Modern Japan - Rath, Eric C., 1967- (Book collections on Project MUSE., 2010)
How did one dine with a shogun? Or make solid gold soup, sculpt with a fish, or turn seaweed into a symbol of happiness? In this fresh look at Japanese culinary history, Eric Rath delves into the writings of medieval and early modern Japanese chefs to answer these and otehr provocative questions.